Potensi Ekstrak Daun Afrika (Vernonia amygdalina), Daun Pepaya (Carica papaya L) Serta Kombinasi Kedua Ekstrak Terhadap Jumlah Folikel Primer, Sekunder dan Tersier Pada Mencit (Mus musculus) - Sukarjati Sukarjati; Ganda Adi Nugroho (WAHANA, 2021)
African leaf (Vernonia amygdalina) and papaya leaf (Carica papaya L) are plants that contain secondary metabolites and are thought to have antifertility effects. V amygdalina and C papaya L leaves contain flavonoids, saponins, tannins, and alkaloids. The purpose of this study was to prove that V amygdalina leaf extract, C papaya L leaf and the combination of the two extracts could reduce the number of primary, secondary and tertiary follicles. This study used 44 female mice. Extraction was carried out by maceration . The doses of V amygdalina leaf extract and C papaya L leaf extract used were 150 mg/kg BW, 200 mg/kg. kg BW, 250 mg/kg BW and the combined doses of V amygdalina leaf extract and C papaya leaf were 75:75 mg/kg BW, 100:100 mg/kg BW, and 125:125 mg/kg BW. The positive control used KB Andalan with a dose of 0.000078 mg. Ovarian histology was made according to laboratory standards Data were analyzed using One-Way ANOVA tand LSD test. The results showed that the administration of V amygdalina leaf extract, C papaya leaf, and their combination significantly affected the decrease in the number of primary follicles (P= 0.03), secondary follicles (P=0.032) and tertiary follicles (P=0.033). The combination extract of V amygdalina leaf and C papaya leaf at a dose of 125:125 mg/kg BW has the most potential as a natural contraceptive ingredient.